The Influence of Interest in K-Pop Idols on Increasing the Motivation to Read Alternative Universe Fiction Works among K-Pop Fans - Hardila, Dinda Sri Wahyu; Ardoni, Ardoni (Journal of Multidisciplinary Science: MIKAILALSYS, 2026)
The rapid development of digital literacy culture among young people has been shaped by the growing popularity of K-Pop culture and the consumption of Alternative Universe (AU) fiction on social media platforms. This phenomenon indicates that reading practices are no longer limited to academic or conventional materials but have increasingly expanded through fandom-based digital media. This study aims to analyze the influence of interest in K-Pop idols on the motivation to read AU fiction among K-Pop fans. A quantitative approach with a descriptive method was employed. The population consisted of 82,425 followers of the X account @Localauniverse, from which 102 respondents were selected through simple random sampling using the Slovin formula. Data were collected using closed-ended questionnaires based on a four-point Likert scale and analyzed through normality testing, linearity testing, simple linear regression, and coefficient of determination analysis using SPSS version 25. The findings reveal that interest in K-Pop idols has a positive and significant influence on the motivation to read AU fiction, as indicated by a significance value of 0.000 (< 0.05) and a regression coefficient of 0.573. The coefficient of determination value of 0.228 further indicates that interest in K-Pop idols contributes 22.8% to reading motivation, while the remaining proportion is influenced by factors beyond the scope of this study. The study concludes that emotional attachment, parasocial relationships, and participation in digital fandom culture play an important role in strengthening fans’ motivation to engage with AU fiction. These findings contribute to the literature on digital literacy, fandom-based reading practices, and youth reading motivation by demonstrating how popular culture and digital media can serve as alternative strategies for promoting reading engagement among younger generations.